Simulasi Peningkatan Lebar Tegangan Input Buck-Boost Converter Dengan Perancangan Coupled Inductor - Tivani M. Christien DS; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This paper describes the design and simulation of a dc-dc buck-boost converter using the buck-boost coupled inductor topology to equalize the dc input voltage source to the load voltage with a wide voltage conversion range. The buck-boost converter coupled inductor system with a closed circuit that is controlled by PI control, voltage mode control, and current mode control on the PWM (Pulse Width Modulation). This circuit is simulated using the PSIM software, and the outputs are analyzed then compared to a buck-boost converter that does not use a coupled inductor. It is indicated that the buck-boost converter without coupled inductor has an input voltage width in the range of 4-21 Volt result in the output voltage of 14 Volt, while a converter using a coupled inductor has an input voltage width in the range of 3-64 Volt, and it generates the steady output voltage of 14 Volt. Key Words: buck and boost converter, coupled inductor, PWM, voltage-mode control, current-mode control, PI control.